Does the withdrawal time affect adenoma detection in non-screening colonoscopies?. Issue 1 (16th March 2019) - Al-Rifaie, Ammar; El-Feki, Mohammed; Al-Talib, Ismaeel; Abdulwahid, Maysam; Hopper, Andrew; Thoufeeq, Mo
Abstract : Aims: There are no studies looking at the relationship between colonoscopy withdrawal time (CWT) and adenoma detection rate (ADR) in non-screening patients. Our aim is to explore the relationship between CWT and ADR, particularly in the proximal colon where colonoscopy is shown to be less protective for the development of cancers. Methods: This is a retrospective study during November 2015 to December 2016 of non-screening colonoscopies done at a large teaching hospital. Incomplete and therapeutic procedures were excluded. The 39 endoscopists included were 15 gastroenterologists, 10 colorectal surgeons and 14 trainee colonoscopists. CWT was calculated by reviewing caecal intubation and rectal retroflexion images. Results: 783 colonoscopies were included, with mean patient age of 58.51 years (SD 15.5). The mean ADR was 21.45% in the study. The CWT could be calculated for 62.83% of the cases (n=492). 80% (393) of colonoscopies had CWT of ≥6 min. Mean CWT was 9.15 min (SD 4.4). The ADR positively correlated with longer CWT (r=0.31, p=0.0001). The ADR was significantly higher when CWT was ≥8 min compared with CWT <6 min or CWT of 6–8 min (p=0.0001). More polyps were detected in the proximal colon when CWT ≥8 min (p=0.078). Mean CWT of gastroenterologists was 9.8 min (SD 4.5), similar to the trainee group (10.3 min, SD 3.8), while mean CWT for colorectal surgeons was 5.7 min (SD 3.2). The ADR for gastroenterologists was 25.9% versus 17.5% for colorectal surgeons and 17.8% for trainees. Conclusions: There is a moderately strong positive correlation between longer CWT and ADR in non-screening colonoscopies. CWT can differ between different endoscopists. Meticulous colonoscopy withdrawal may improve polyp detection in the proximal colon.